Mathematical simulations for better aquifer management - Bittinger, Morton W., author; Longenbaugh, R. A. (Robert A.), author; Duke, Harold R. (Harold Ray), 1940-, author; International Association of Hydrological Sciences, publisher (Colorado State University. Libraries, 1967)
Manipulation of groundwater storage in conjunction with surface water supplies often requires simultaneous consideration of varied aquifer hydraulic and geometric characteristics, highly variable pumping patterns in time and space, imperfectly connected bodies of surface water and non-deterministic natural recharge. In addition, legal, economic and social conditions impose constraints which must be considered in aquifer operation and management. This paper describes mathematical modeling and computer analysis techniques that allow consideration of the many varied and changing factors mentioned above. Application is made to specific aquifer management problems.
CER-66-67 MWB 10.
Extract of publication no. 72 of the I.A.S.H. Symposium of Haifa.
Keywords: Aquifers -- Mathematical models; Aquifers -- Simulation methods; Aquifers -- Management